Sector update. Library information services. - Singh R (Information World Review, 2005)
The modern information department and library need the latest tools and services to operate effectively. Library systems must include link resolvers, access to electronic journals and current subscriptions. This month's Sector Update draws together a wide range of library serices, including document delivery, journal subscriptions and book data. Compiled by Rachael Singh.